2002
DOI: 10.1007/s004020100314
|View full text |Cite
|
Sign up to set email alerts
|

Adjacent segment degeneration after lumbar spinal posterolateral fusion with instrumentation in elderly patients

Abstract: This retrospective study investigated adjacent segments radiologically and clinically after posterolateral fusion of the lumbar spine with instrumentation. Thirty-two patients over 60 years old with a postoperative follow-up of at least 4 years were included. These patients all met the criteria of a postoperative symptom-free period of over 2 years, evident fusion mass seen on plain radiographs, and no implant breakage or loosening. There was 81.3% excellent and good clinical results (26/32). For all patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(68 citation statements)
references
References 9 publications
1
64
1
2
Order By: Relevance
“…'Adjacent segment disease' has been used to designate the development of new clinical symptoms that are compatible with radiographic changes adjacent to the level of a previous spinal fusion. Although studies on the adjacent segment problem are now in active progress, but most of them have utilized radiographic findings as a diagnostic tool rather than for symptomatology [2,5,[7][8][9][10]19]. However, we suggest that discussion about the adjacent segment changes irrelevant to clinical findings is not so meaningful.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…'Adjacent segment disease' has been used to designate the development of new clinical symptoms that are compatible with radiographic changes adjacent to the level of a previous spinal fusion. Although studies on the adjacent segment problem are now in active progress, but most of them have utilized radiographic findings as a diagnostic tool rather than for symptomatology [2,5,[7][8][9][10]19]. However, we suggest that discussion about the adjacent segment changes irrelevant to clinical findings is not so meaningful.…”
Section: Discussionmentioning
confidence: 87%
“…We also found that the incidence of distal ASD was much lower than that of proximal ASD. The exact statistical data have not been collected, but several other clinical studies have demonstrated similar tendencies [1,2,5,7]. This may be due to the recessed position of the L5-S1 segment within the pelvis restrained by iliolumbar ligaments [9].…”
Section: Discussionmentioning
confidence: 99%
“…While the evolution and prevalence of ASD are not fully known, there is increasing evidence in literature that its effects may be seen soon after fusion surgery and in as many as 30 % of patients [3,4]. Cheh et al reported a rate of clinical ASD of 30.3 % and showed that patients in whom adjacent level disease developed had significantly worse Oswestry Disability Index scores than those without adjacent level disease.…”
Section: Discussionmentioning
confidence: 99%
“…Achievement of fusion may, in fact, have long-term effects on the immediately adjacent motion segments [3,4]. At the junction with adjacent mobile segments, the rigidity of the fused segments induces increased constraints that can constitute a clinical concern [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[1] Several studies in the recent literature questioned the efficacy of spinal fusion in the treatment of low back pain. [2] In addition, a significant apprehension of adjacent segment disease in the long term follow-up after spinal fusion always concerned the spinal [3][4][5][6][7][8] surgeon.…”
Section: Introductionmentioning
confidence: 99%